Don Cossacks-Kalmyks: from Nomadism to settled way of life - V. A. Dronov (Nomadic Civilization: Historical Research)
The article deals with the life of the Kalmyks who lived on the territory of the Don Cossacks in the 17th–early 20th centuries. The processes of isolation of the resettled Kalmyks on the Don land, gradual entry into the political and socio-economic space of the Don Cossacks are studied. A signiﬁcant contribution of the Don Kalmyks to the socioeconomic development of the Cossack region, the protection of the Russian Empire from external encroachments is noted. The subject of the study is the system of measures taken by the leadership of the Don Cossacks in order to transition the Kalmyks from nomadism to settled life. The features of the transition of the Don Kalmyks to sedentary life as a result of the sedentarization policy pursued by the authorities, the main goal of which was to change the economy, life, social structure of the Kalmyk-Cossacks, their full inclusion in the general economic and cultural activities of the region, are traced. Particular attention is paid to the study of changes in the economy, spiritual life, mentality of the Don Kalmyks. The experience of management and cultural and spiritual interaction of the Don Kalmyks with the Cossacks, accumulated by the nomads during their three-century residence on the territory of the Don Cossacks, is considered. It is emphasized that this invaluable experience helped the Don Kalmyks to quickly adapt and painlessly engage in socioeconomic transformations in the Kalmyk Autonomous Region, where they were resettled in the 20s and 30s of the last century by a government decision. The conclusion is made about the positive impact of the Don Kalmyks who have settled down to settled life on the accelerated process of settling in the KAO. The research materials can be useful for students, graduate students, researchers, teachers of schools, educational institutions, all those who are interested in the history of the Don region, the Don Kalmyks.